The Use of Acellular Dermal Matrix (Integra Single Layer) for the Correction of Malformative Chest Wall Deformities: First Case Series Reported - Delgado-Miguel, Carlos; Miguel-Ferrero, Miriam; Muñoz-Serrano, Antonio; Díaz, Mercedes; López-Gutiérrez, Juan Carlos; Torre, Carlos De la (The Surgery Journal, 2022)
Introduction Autologous tissue transfers have been used in chest wall reconstruction for decades, with high morbidity. Recently, acellular dermal matrices (ADMs) have emerged as an alternative. The aim of this article is to report our initial experience in the reconstruction of malformative chest wall deformities with ADM.Methods A prospective observational study was performed in patients with malformative chest wall deformities, who were reconstructed with ADM at our institution between 2018 and 2020. We analyzed demographic variables, surgical features, postoperative complications, and cosmetic results at 12 months' follow- up.Results Four male patients were included (median age: 16 years). Two patients had bilateral costal anomalies, one patient had a unilateral chest deformity, and one patient had Poland syndrome. In all patients, blunt dissection of the subcutaneous cellular tissue overlying the defect was performed through 2.5 to 3 cm skin incisions, creating a pouch. Afterwards, several sheets of Integra Single Layer were placed in the pouch, to replace the volume defect. All patients were discharged same-day. No postoperative infections, hematomas, or seromas were observed. Only one patient presented with a partial surgical wound dehiscence. Revisions were performed at 1, 3, 6, and 12 months. All 4 patients were satisfied with the cosmetic outcome (Nuss Questionnaire: median score: 16 points; Q1–Q3: 22–26).Conclusion The use of ADM in malformative chest wall deformities reconstruction has not been previously described in children. This study demonstrates that the use of ADM is a safe and reliable technique. However, more studies with long-term follow-up are warranted.
Keywords: minimally invasive surgery; chest wall deformities; children; Poland syndrome